KfW/ZEW CO2 Barometer 2015 – Carbon Edition. Ten years of emission trading: strategies of German companies - Carlo Gallier; Peter Heindl; Daniel Osberghaus; Karl Ludwig Brockmann; Caroline Dieckhöner (KfW Bankengruppe und Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
German companies participating in the EU Emissions Trading Scheme (EU ETS) analyse the consequences of climate policy on their competitiveness in a variety of ways. When asked whether global climate policy - e. g. decisions adopted at UN climate negotiations - negatively impacted on their competitiveness, 39 per cent of the respondents gave a positive response. 53 per cent of companies expect European climate protection rules, such as the EU ETS, to have a negative impact on competitiveness. Climate policy at the national level, the turnaround in German Energy Policy (the so-called energy transition), for example, is perceived as being potentially damaging by 59 per cent of companies. This is one of the findings of the KfW/ZEW CO2 Barometer 2015, an annual survey conducted by KfW bank in cooperation with the Centre for European Economic Research (ZEW), since 2009. The survey analyses the impact of the EU ETS on the companies regulated. The variation in the ways in which companies estimate the impact of climate policy on their competitiveness, is particularly pronounced amongst companies which are in international competition. Only around 15 per cent of the firms regulated by EU ETS, however, assume that the impending 2015 UN climate negotiations held in Paris this December, will lead to a binding international agreement. In view of the continuous fall in the price of carbon allowances, the EU has adopted a market stability reserve (MSR) in order to reduce the surplus of carbon credits (estimated at over 2 billion). In the course of this initiative, in the second half of 2014 and in the first half of 2015, the price of carbon allowances slightly increased. The price recorded in August 2015 was approximately EUR 8 per tonne of CO2 - the highest price recorded since November 2012. In view of this trend, German-based companies involved in this survey have, in comparison with last year's survey, adjusted their short, middle, and long-term price expectations upwards. The inflation-adjusted price is accordingly expected to stand at EUR 7.82 per tonne of CO2 in December 2015. It is estimated, that the price will increase to EUR 15.92 by 2020, and reach EUR 25.45 by 2030. As price expectations remain below EUR 30 per tonne of CO2, the surveyed companies still consider it unlikely that any real incentives to sustainably cut emissions will be created. In 2014, a majority of 76 per cent of companies, invested in the reduction of carbon emissions or shifted to green production processes. As previous studies have shown, however, only ten per cent of the responding companies actually had the objective of cutting carbon emissions. Process optimisation and investments in energy efficiency were the main motivations for any climate commitments made. The KfW/ZEW CO2 Barometer is a joint project between KfW bank and ZEW. Since 2009, the project has served to analyse the impact of the European Emissions Trading System (EU ETS) on companies in Germany. Around 800 companies are invited to participate in the annual survey. On average, 140 companies each year provide information about their current situation and future strategies.
Keywords: 330; Emissions trading; Climate policy